2023
DOI: 10.1093/sleep/zsad206
|View full text |Cite
|
Sign up to set email alerts
|

The effects of closed-loop auditory stimulation on sleep oscillatory dynamics in relation to motor procedural memory consolidation

Abstract: Study Objectives Healthy aging and many disorders show reduced sleep-dependent memory consolidation and corresponding alterations in non-rapid eye movement sleep oscillations. Yet sleep physiology remains a relatively neglected target for improving memory. We evaluated the effects of closed-loop auditory stimulation during sleep (CLASS) on slow oscillations (SOs), sleep spindles, and their coupling, all in relation to motor procedural memory consolidation. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 72 publications
1
1
0
Order By: Relevance
“…Accordingly, prior research has used experimental interventions to target plasticity processes during this window and, in turn, influence memory consolidation during sleep. In line with our findings, this earlier research has collectively shown that stimulating SO at the up-phase of the slowoscillation enhanced the amplitude of ongoing SOs [17][18][19][20][21][25][26][27]29,33 , sigma oscillation power during the ascending phase of the SO [18][19][20] and memory consolidation [17][18][19][20][21]26,27 . Interestingly, the time-locking of the sigma burst to the up-phase of the SO has been shown to predict a positive outcome of consolidation 14,34 .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Accordingly, prior research has used experimental interventions to target plasticity processes during this window and, in turn, influence memory consolidation during sleep. In line with our findings, this earlier research has collectively shown that stimulating SO at the up-phase of the slowoscillation enhanced the amplitude of ongoing SOs [17][18][19][20][21][25][26][27]29,33 , sigma oscillation power during the ascending phase of the SO [18][19][20] and memory consolidation [17][18][19][20][21]26,27 . Interestingly, the time-locking of the sigma burst to the up-phase of the SO has been shown to predict a positive outcome of consolidation 14,34 .…”
Section: Discussionsupporting
confidence: 93%
“…These phase-specific effects are in line with previous studies in which acoustic stimulations delivered in a closed-loop fashion at the up-phase (or during the down-to-up transition) of the SO have been shown to enhance declarative memory consolidation 17,20,21,[25][26][27] (but see 26,28 for null effects). We are only aware of one study using closed-loop acoustic stimulation in the motor memory domain and results showed no benefit of SO upstimulation on motor performance 29 . The discrepancy between this recent research and our findings is unclear but we speculate that methodological differences between studies, such as time afforded in NREM sleep (nap vs. night paradigm) or stimulation phase (380ms post-trough vs. peak), might have contributed to these inconsistencies.…”
Section: Discussionmentioning
confidence: 99%